Child Education in the Household Islamic Education Management Perspective - Halimatussakdiah Halimatussakdiah (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2023)
The purpose of writing this article is to reveal the basic concepts of Islamic Education for children at the golden age (0-6 years) and reveal the concept of Management of Islamic Education for children aged 0-2 years in households. The method used is descriptive-qualitative through library research and documentary techniques which are then analyzed using the Content Analysis method. Based on the results of the study it was found that; the concept of Management of Islamic Education for early childhood in the household, includes: (1) Planning (planning) of Islamic education which refers to the theory of W5 1 H (What, who, when, where, why, and how), and is carried out in the household by the main teacher namely parents (father and mother) and family. (2) Implementation (actuating) on the basis of the Qur'an, al-Sunnah and Ijtihad), educational goals (physical, spiritual, and intellectual), educational methods (models, habituation and training, advice/reward, supervision, punishment/ penalty). (3) Evaluation (controlling) of various aspects in accordance with the goals and competency standards of Early Childhood Education that have been determined, namely: (a) moral aspects and religious values, (b) social, emotional and independence aspects, (c) language aspects, (d) cognitive aspects, (e) physical/motor aspects, and (f) artistic aspects. Tujuan penulisan artikel ini adalah untuk mengungkap konsep dasar Pendidikan Islam bagi anak pada usia keemasan (0-6 tahun) dan mengungkap konsep Manajemen Pendidikan Islam bagi anak usia 0-2 tahun di rumah tangga. Metode yang digunakan yaitu deskriptif- kualitatif melalui studi kepustakaan (library research) dan teknik dokumenter yang selanjutnya dianalisis dengan métode Content Analisis. Berdasarkan hasil penelitian diperoleh bahwa; konsep Manajemen Pendidikan islam bagi anak usia dini di rumah tangga, meliputi: (1) Perencanaan (planning) pendidikan Islam yang mengacu pada teori W5 1 H (What,who, when, where, why, and how), dan dilakukan di rumah tangga oleh guru utamanya yaitu orang tua (ayah dan ibu) serta keluarga. (2) Pelaksanaan (actuating) dengan dasar Al-Qur’an, al-Sunnah dan Ijtihad), tujuan pendidikan (jasmani, rohani, dan akal), metode pendidikan (teladan, pembiasaan dan latihan, nasehat/ penghargaan, pengawasan, hukuman/ sanksi). (3) Evaluasi (controlling) dari berbagai aspek sesuai dengan tujuan dan standar kompetensi Pendidikan Anak Usia Dini yang telah ditentukan, yaitu: (a) aspek moral dan nilai-nilai agama, (b) aspek sosial, emosional dan kemandirian, (c) aspek bahasa, (d) aspek kognitif, (e) aspek fisik/ motorik, dan (f) aspek seni.